Milly, Molly and Taffy Bogle - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
A quiet walk with Taffy Bogle turns into an adventure Milly and Molly will never forget. Suggested level: junior